The Effectiveness of Learning By Teaching (LBT): A Case of Junior High School Students Studying Tenses - Michael Setiawan (Bina Nusantara University, 2019)
This research aimed to see if learning by teaching (LBT) could really be implemented in classrooms. This case study intended to discover if LBT was applicable to teach tenses. This quantitative research involved 50 students from the two of 8th grade classes in one junior high school in Jakarta, one of which acted as the control group and the other one as the experimental group. This research focused on the learning of five tenses, namely the simple present tense, the simple past tense, the simple future tense, the simple present continuous tense, and the simple present perfect tense. A pre-test was employed before the research started and after the treatment had been given to the experimental group, a post-test was given a week after, and another post-test was given three months later. The results show that LBT helps the subjects learn better. Moreover, they also remember their materials longer. Therefore, LBT can be a good student-centered activity which has been proven successful.